A Happy and Engaged Class Without Cell Phones? It's Easier Than You Think. (October 2016) - Katz, Louise; Lambert, Warren
Although there have been many suggestions for incorporating cell phone use into classroom activities, there have been few suggestions for removing cell phone use from the classroom. This article presents an easy-to-implement method using positive reinforcement that effectively removes cell phones from the classroom in a way that is highly endorsed by students and that greatly fosters student engagement, class participation, and a focused and respectful classroom atmosphere. In a quasi-experiment, we found significant correlations between giving up cell phones and students' test grades, overall grade point average (GPA), semester's GPA, and attendance. Rate of improvement of higher and lower participators suggested that better students were more likely to give up their cell phones to earn an extra point toward their final course grade.